EFEKTIVITAS EDUKASI GIZI BAYI MELALUI PENYULUHAN ASI EKSKLUSIF TERHADAP PENGETAHUAN IBU DI DESA SUGIHWARAS BARAT - Najmah Maulaya; Dina Waldani; Rizki Julianti; Lailatul Rahma Fikry; Vince Miagoni; Maulidya Fazalika; Dinda Rahmah Yani (PARIPALAKA SRIWIJAYA, 2026)
Exclusive breastfeeding during the first six months of an infant’s life is a fundamental intervention in improving nutritional status and preventing stunting, particularly in communities with limited access to health information. In Sugihwaras Barat Village, an educational activity titled “Nourish the Body with Exclusive Breastfeeding” was conducted, targeting 25 breastfeeding mothers at Posyandu Melati. This intervention employed an interactive lecture approach combined with leaflets as a visual educational medium. Evaluation was carried out through pre-test and post-test assessments using identical instruments to measure changes in participants’ knowledge. The results revealed a significant improvement, with 76% of participants classified as having good knowledge and 24% as having sufficient knowledge. Active engagement during discussions and positive reception of the material indicated high acceptance of the educational method. These findings underscore the effectiveness of direct interactive education combined with appropriate supporting media in enhancing public health literacy. Continuous educational efforts involving community health workers are essential to ensure optimal and sustained exclusive breastfeeding practices, thereby contributing to long-term improvements in infant health outcomes.